2019
DOI: 10.1007/s40519-019-00800-x
|View full text |Cite
|
Sign up to set email alerts
|

Psychological predictors of poor weight loss following LSG: relevance of general psychopathology and impulsivity

Abstract: Purpose After bariatric surgery (BS) a significant minority of patients do not reach successful weight loss or tend to regain weight. In recent years, interest for the psychological factors that predict post-surgical weight loss has increased with the objective of developing interventions aimed to ameliorate post-surgical outcomes. In the present study, predictive models of successful or poor weight loss 12 months after BS were investigated considering pre-surgery level of psychopathological symptoms, dysfunct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 76 publications
1
7
0
Order By: Relevance
“…This finding suggests that some psychological variables, like depressive symptoms and food restraining, themselves does not have significantly strong effect on weight loss, but in combination overeating episodes does. Our results support the theory that mildly elevated symptoms of depression do not have effect on post-operative weight loss ( 44 ), while worse clinical manifestations (depression as psychiatric disorder) does ( 43 ). Similar, food restraining alone did not predict weight loss, but in combination with overeating become significant predictor.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This finding suggests that some psychological variables, like depressive symptoms and food restraining, themselves does not have significantly strong effect on weight loss, but in combination overeating episodes does. Our results support the theory that mildly elevated symptoms of depression do not have effect on post-operative weight loss ( 44 ), while worse clinical manifestations (depression as psychiatric disorder) does ( 43 ). Similar, food restraining alone did not predict weight loss, but in combination with overeating become significant predictor.…”
Section: Discussionsupporting
confidence: 86%
“…Previous research has focused mainly on physical and mental health benefits of more invasive bariatric procedures (24). From mental health perspective bariatric surgeries were found to be associated with sustained improvement in quality of life for adolescents with severe obesity, specifically in weight related quality of life and physical health related quality of life (25)(26)(27). Some research studies have also found that after surgical procedure adolescents showed significantly fewer symptoms of anxiety and depression and significantly improved self-concept compared to baseline (27,28).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preoperative predictors of weight loss are poorly defined, and the predictors that have been found explain very little of the overall variance in weight outcomes (24). Some adult data suggest that cognitive and behavioral variables as well as preoperative weight loss may be used to predict postoperative weight loss; however, others have found no correlation (25‐27). We, like others, have demonstrated that most of the weight loss that will occur in adolescents is achieved within the first year following MBS (28).…”
Section: Discussionmentioning
confidence: 99%
“…This reinforces the idea that insulin signaling, which is implicated in metabolism and child growth, also plays a role in neurodevelopment. Previous studies have shown that impulsivity is a core feature of both psychopathology and metabolic diseases ( Schachar and Logan, 1990 ; Silveira et al, 2012 ; Testa et al, 2019 ). Therefore, the interaction described here could be the basis to explain the co-morbidity associated with ELA exposure.…”
Section: Discussionmentioning
confidence: 99%